PERANCANGAN DAN UJI KINERJA SPRINKLER SEDERHANA - Esar Rante Kayangan; Ruland A. Rantung; Leo Kalesaran (COCOS, 2023)
AbstractSprinkler irrigation is a way of watering plants by spraying water into the air andfalling on the ground to resemble rain. Sprinklers are generally applied to commodities withhigh economic value, so sprinkler prices are also quite expensive. Sprinklers currentlycirculating in the market are sold in various models, some can rotate 180 to 360 degrees withdifferent beam distances. The purpose of this research is to design and manufacture a simplesprinkler prototype and examine the performance of the sprinkler prototype that is made. Themethod used is the experimental method and the descriptive analysis method, which focuseson performance testing using the prototype sprinkler that is made. This study used severalcomponents of the equipment such as 6 sprinklers , water pumps and piping networks in aland area of 18 m × 12 m. The variables observed in the study included: water discharge,pump rotation (rpm), uniformity coefficient (CU), jet distance, use of pump fuel. The resultsof this study indicate that the application of sprinkler irrigation water uses 6 sprinklerprototypes that were made and a Korobe WR 20X water pump, with a time of 2 minutes, 6sprinklers can release 154.12 L/minute of water with an average pump speed of 3,758. 33RPM and spent as much as 45 ml/minute of fuel. The farthest distance of the sprinkler beamis 3.5 meters.Keywords: design, performance test, sprinkler, radiance, water discharge